Validation of the PILL-5: A 5-Item Patient Reported Outcome Measure for Pill Dysphagia - Nativ-Zeltzer, Nogah; Bayoumi, Ahmed; Mandin, Van Pierre; Kaufman, Matthew; Seeni, Indulaxmi; Kuhn, Maggie A.; Belafsky, Peter C. (Frontiers in Surgery, 2019)
Objectives: Pill dysphagia is common and costly with a significant risk of pill retention, caustic injury, and poor medication compliance. The purpose of this investigation was to determine the validity and reliability of the PILL-5, a self-administered patient reported outcome measure (PROM) to quantify the degree of pill (tablet and capsule) dysphagia. The Pill-5 is a 5-item questionnaire with a maximum symptom score of 20. Methods: The PILL-5 was administered to 190 patients with dysphagia referred for videofluoroscopic esophagography (VFE). Construct validity was assessed by comparing PILL-5 composite scores to delayed barium tablet transit on VFE. Normative data was obtained by administering the instrument to a cohort of healthy community based volunteers. Internal consistency was assessed with the Cronbach alpha. Test/retest reliability was determined by administering the instrument to the same cohort of patients at two time points. Results: The mean PILL-5 was 5.6 (± 4.9) for persons with dysphagia and 1.6 (±2.7) for healthy volunteers (p < 0.001). The internal consistency of the instrument was high (Cronbach alpha = 0.85). The mean PILL-5 was 4.3 (± 4.1) for patients with normal transit and 7.6 (± 5.3) for patients with delayed barium tablet transit on esophagography, indicating excellent criterion based validity (p < 0.001). Reproducibility was high with an intraclass correlation coefficient of 0.83 (p < 0.001). Conclusions: Healthy individuals report some degree of swallowing difficulty with pills. Normative data suggest that a Pill-5 > 6 is abnormal (mean + 2 SD). The instrument demonstrated excellent criterion based validity and reliability. The PILL-5 is the first validated patient reported outcome measure for pill dysphagia.